Jurists’ language or citizens’ language? Some remarks on legal language - de Prada García, Aurelio (EUNOMÍA. Revista en Cultura de la Legalidad, 2014)
This paper focuses on the secular dispute about the nature of legal language. Should it be a specialized language or a common language, the language of laymen, so to speak? Its conclusion is that legal language should be both the language of jurists and that of citizens.
Keywords: Democracy; legal language; jurist; citizen